Sexual activity in British men’s prisons: a culture of denial - Stevens, Alicia (The British journal of criminology, 2017)
Theorized through Stanley Cohen’s sociology of denial and informed by testimonies from formerly imprisoned men, this article argues that a culture of denial limits the ability and willingness of prison authorities and prison staff to recognize, acknowledge and respond appropriately to the realities of sexual activity in British prisons. It has three objectives: to detail experiences of consensual and coercive sex; to elucidate the collective and collaborative cultural habit of ‘don’t ask, don’t tell’ by which what is known becomes not known and what is concealed remains hidden; and to show how this strategy leaves unprotected those who choose to engage in, or are coerced into, sexual activity.